Implementation of Mindful Self-Compassion Group Counseling in Reducing Self-Injury Behavior in Students - Thessia Permata Bunda; Yarmis Syukur; Dina Sukma; Miftahul Fikri (Postgraduate, University of Mataram, 2025)
Self-injury behavior is still found among students, especially in junior high school environments. Of course, this should be a concern for parents, schools, and especially Guidance and Counseling teachers to reduce self-injury behavior in students. This study aims to determine the effectiveness of the application of mindful self-compassion group counseling in reducing self-injury behavior in students. The research method uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 9 eighth-grade students who had self-injury behavior, selected using a purposive sampling technique. The research instrument used a self-injury behavior questionnaire with a Likert scale. The intervention was carried out through eight mindful self-compassion group counseling sessions. Data were analyzed using the Wilcoxon signed ranks test. The results of the study showed that: there was a significant difference in self-injury behavior of students before and after being given mindful self-compassion group counseling treatment; the posttest score was lower than the pretest score; there was a significant decrease in self-injury behavior of students before and after being given mindful self-compassion group counseling treatment. Based on the results of the study, mindful self-compassion is quite effective in reducing self-injury behavior in students.